Analisis Pemahaman Siswa SD IT A-l-Khoiriyah Al-Husna dalam Membaca Cerita - Alwiyan Wijaya; Astri Sutisnawati; Dyah Lyesmaya (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This study aims to (1) find out the understanding of fourth grade students of SD IT Al-Khoiriyah Al-Husna in reading stories (2) find efforts / solutions to improve students' understanding of grade IV SD IT Al-Khoiriyah Al-Husna in reading stories. This type of research is qualitative descriptive. Data collection in this research is by test, interview and documentation. The subjects of this study were the fourth grade students of Al-Khoiriyah Al-Husna Elementary School, totaling 28 students. While the object of this research is students' understanding in reading stories. The results showed that students who were able to answer questions more than 50% on the indicator (1) Identifying themes in the reading as much as 85%, (2) Identifying the main points in reading as much as 75%, (3) Mentioning the names figures in reading as much as 82%, (4) Identifying the nature / character of characters in reading as much as 85% (5) Mentioning background / place in reading as much as 75%, and (6) Finding information in the text through reading activities as much as 60%. Whereas for students who have not been able to answer questions less than 50%, the indicator (7) explains the mandate / message in the story as much as 36%, and (8) concludes the reading contents in coherent and communicative language as much as 36%. Teacher's efforts / solutions to improve students' understanding in reading stories, that is, teachers do a variety of ways and guide students to practice reading then are identified by students.